1986
DOI: 10.1099/00221287-132-6-1459
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Diploid Self-sporulating Cycle in the Basidiomycetous Yeast Rhodosporidium toruloides

Abstract: ~ Self-sporulating diploid and aneuploid cells were identified in the life cycle of Rhodosporidium toruloides by microscopic observation of nuclear behaviour, microphotometry of DNA content, and genetic characterization of progeny. From a sexual cross between haploid A -and a-type strains, diploid progeny with both A and a mating-type loci and aneuploid progeny with either A or a mating-type locus were isolated in addition to haploid progeny. The diploid isolates propagated by budding in yeast form and eventua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
2
1
0
Order By: Relevance
“…Self-fertile and asexual strains can be found among natural isolates of red yeasts of the Sporidiobolales [40] , [41] and the origin of the first may be related to the occasional formation of diploid yeast strains. In addition to our present observations, the formation of diploid strains was also previously reported in R. toruloides [51] . However in none of the species studied so far are these diploid states prevailing, leading to the presumption that although these strains do not exhibit obvious growth defects, their genetic makeup may carry some selective disadvantages.…”
Section: Resultssupporting
confidence: 91%
“…Self-fertile and asexual strains can be found among natural isolates of red yeasts of the Sporidiobolales [40] , [41] and the origin of the first may be related to the occasional formation of diploid yeast strains. In addition to our present observations, the formation of diploid strains was also previously reported in R. toruloides [51] . However in none of the species studied so far are these diploid states prevailing, leading to the presumption that although these strains do not exhibit obvious growth defects, their genetic makeup may carry some selective disadvantages.…”
Section: Resultssupporting
confidence: 91%
“…These two haploid strains of R. toruloides are very divergent [16] , sharing only 87% identity in genomic nucleotide sequences, despite the fact that they can mate as exemplified by the type strain of R. toruloides [20] . The CGMCC 2.1609 genome sequenced here contains only A1 mating-type information [21] , [22] , which is consistent with aneuploidy observed in progeny from such a mating [23] .…”
Section: Experimental Design Materials and Methodssupporting
confidence: 82%
“…In some cases, aneuploid offspring is also a result of chromosomal nondisjunction and non-reciprocal genetic exchanges between the two parental genomes (Dujon, 2010;Gilchrist & Stelkens, 2019). Abe and Sasakuma (1986) identified a diploid self-sporulating cycle in R. toruloides. In that study, cells were observed as diploid or aneuploid in addition to haploid progeny after a sexual cross between the compatible mating types (A1 and A2).…”
Section: Ploidy Levelsmentioning
confidence: 99%